Interleukin-4 and immunoglobulin E levels in newborns at risk of atopic diseases - Frengky Sutanto; Rocky Wilar; Diana Devi Sondakh (Paediatrica Indonesiana, 2011)
Background The clinical syndrome of atopy is associated v.ith the production of immunoglobulin E (lgE) in response to antigenic stimulation as part of a type I hypersensitivity reaction. Since early prevention is regarded as an important cornerstone in the management of atopic diseases, the identification of reliable markers such as IgE and interleukin 4 (IL-4) in detecting individuals at risk are of major interest.Objective To determine whether cord blood IgE and IL-4 levels can be used as an predictor of atopy in newborns with a family history of atopic diseases.Methods We conducted a cross-sectional study on healthy-term newborns in the neonatal ward at R.D. Kandou Hospital from June to August 2010. A total of 50 healthy newborns in atopic and non-atopic groups were examined for cord blood IgE and IIA levels.Result The mean cord blood ILA levels in the atopic and non-atopic groups were 0.1 Î¼g/mL (SD 0.08) and 0.1 Î¼g/mL (SD 0.16) (P=0.359), respectively. The mean cord blood IgE levels in the atopic and non-atopic groups were 2.2 IU/mL (SD 1.98) and 0.5 IU/mL (SD 0.29) (P<0.00l), respectively. A point-biserial correlation coefficient analysis showed no significant correlation between ILA levels and family history of atopic disease (rpb=0.098), and a weak correlation between IgE levels and family history of atopic disease (rpb=0.54).Conclusions Cord blood IgE and IL-4 levels should not be used to distinguish newborns with a family history of atopic diseases from those without.